Side-effects Associated with Gel Nail Polish: A Self-questionnaire Study of 2,118 Respondents - Justyna Putek; Tomasz Przybyla; Jacek C. Szepietowski; Wojciech Baran; Aleksandra Batycka-Baran (Medical Journals Sweden, 2020)
Gel nail polish is commonly used in manicures; however, research into the side-effects of gel nail polish is scarce and focusses mainly on allergic contact dermatitis. The aim of this study was to assess the frequency and characteristics of side-effects associated with use of gel nail polish. A self-questionnaire survey was conducted on a representative sample of individuals (n = 2,118, all female). Of these, 48.3% reported side-effects while applying gel nail polish, approximately 20% during wearing it, and more than 75% after removing the polish. Frequency of changes in the nail plates was significantly higher after removing the gel nail polish than when applying or wearing it (p < 0.0001). Frequency of changes in the nail plates was associated with whether the procedure was performed by professionals or non-professionals. Education about the risk of side-effects and sensitization is crucial for people using gel nail polish.